Authentic materials for the language classroom: Digitised texts via email attachments. - Ann Rosnida Mohd Deni, *; Zainor Izat Zainal, (MELTA, 2009)
For many language teachers, the Internet has brought an endless supply of authentic, real world, up-to-date materials into their classrooms. Such incorporation of Internet materials into the language classrooms has improved learning and teaching in many ways and has empowered many students to become critical thinkers in learning. Internet materials that can be utilised in the language classrooms can be derived not only from various reliable websites but also from communication tools like emails, newsgroups and texts, and also audio and video conferencing. Digitised texts that are obtained via email attachments can also be a creative resource for language teachers. These texts that come in various modes cost practically nothing and most of them can be modified and adapted to suit different levels and types of students. This paper considers the following: authentic features of digitised texts transmitted via email attachments; the rationale for using these authentic materials in a language classroom; pedagogical considerations to be addressed before the utilisation of these texts; and a language teacher’s experience in incorporating digitised authentic texts in her language classroom.